The Emerald handbook of multi-stakeholder communication : emerging issues for corporate identity, branding and reputation - Foroudi, Pantea, 1974-; Nguyen, Bang; Melewar, T. C. (Emerald Publishing Limited, 2022)
Even before the outbreak of COVID-19, scholars and marketers alike were paying increased attention to the complex array of stakeholders that corporations need to address to maintain a strong brand, identity, and reputation. To date, however, little empirical research into these issues has been published, and no single work has taken stock of the major changes in the field of stakeholder communication as they apply to corporate branding. The Emerald Handbook of Multi-Stakeholder Communication gathers an international, multidisciplinary team of experts to present just such sorely needed insight into effective brand messaging for multiple stakeholders, all while utilizing a diverse array of theoretical and methodological approaches that cumulatively present an up-to-date overview of the whole field. Starting with an introductory section on corporate messaging in a post-COVID era, chapters cover branding, identity, and reputation, respectively before covering differing marketing approaches and building a concluding reflection on future challenges and opportunities. These chapters offer comparative analyses of many different types of stakeholders from all over the globe. B2C, B2B, C2C and P2P contexts are all considered, as are recent developments in the field related to social media relations, sustainability and inclusivity, and virtual, mixed, and augmented reality. This comprehensive handbook is a must-have resource not only for students and researchers in business, management, brand management, communication, consumer behaviour, and marketing, but also for marketing practitioners, advertising and PR practitioners, and business consultants.